2003
DOI: 10.1086/367777
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Find DUP25 in Patients with Anxiety Disorders, in Control Individuals, or in Previously Reported Positive Control Cell Lines

Abstract: Investigation of the co-occurrence of panic and phobic disorders with joint laxity led to the identification of various forms of interstitial duplications involving human chromosome 15q24-q26 (named "DUP25") in a Spanish population. DUP25 was observed in 68 of 70 (97%) patients assigned the diagnosis panic disorder/agoraphobia. DUP25 was also found in 14 of 189 (7%) control individuals. In the present study, we replicated the experimental conditions described by Gratacòs and colleagues in which fluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 5 publications
5
31
1
2
Order By: Relevance
“…By broadening the phenotype even more, including comorbid anxiety disorder, childhood anxiety disorders, or continuous anxiety disorder diagnosis since age 13, the authors observed evidence for linkage to chromosome 10q. Finally, a Spanish group detected the presence of a large interstitial duplication of chromosome 15q24-26 in pedigrees segregating PD and joint laxity (Gratacos et al, 2001), a finding that was not replicated in another sample (Tabiner et al, 2003). Oddly, evidence for linkage between this duplication and panic occurred when the phenotype was maximally broadened to comprise PD, AG, joint laxity, and social phobia (lod B5).…”
Section: Discussionmentioning
confidence: 99%
“…By broadening the phenotype even more, including comorbid anxiety disorder, childhood anxiety disorders, or continuous anxiety disorder diagnosis since age 13, the authors observed evidence for linkage to chromosome 10q. Finally, a Spanish group detected the presence of a large interstitial duplication of chromosome 15q24-26 in pedigrees segregating PD and joint laxity (Gratacos et al, 2001), a finding that was not replicated in another sample (Tabiner et al, 2003). Oddly, evidence for linkage between this duplication and panic occurred when the phenotype was maximally broadened to comprise PD, AG, joint laxity, and social phobia (lod B5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover interstitial duplications in 15q24-26, engulfing Lingo-1 in its entirety, have been significantly associated with panic, agoraphobia and social phobia in families, and with panic disorder in non-familial cases, with 90% of patients fitting the diagnosis of one or more of the anxiety disorders having the chromosomic duplication (Gratacòs et al, 2001). Despite a number of groups trying to reproduce this finding, none have successfully done so (Henrichsen et al, 2004;Tabiner et al, 2003;Weiland et al, 2003;Zhu et al, 2004), therefore the finding by Gratacòs et. al.…”
Section: Lingo-1 Signaling: a New Role In Psychiatric Disordersmentioning
confidence: 99%
“…The observation both here and elsewhere (Depinet et al 1997) that rearrangements which lead to neocentromere emergence on chromosome 15 are mitotic in origin is interesting in this respect, as mitotic instability of the DUP25 duplicons has already been reported within a clinical context . However, the latter data were recently questioned by Tabiner et al (2003).…”
Section: Duplicons and Neocentromere Emergence On 15qmentioning
confidence: 99%